2016
DOI: 10.1109/tsg.2015.2426017
|View full text |Cite
|
Sign up to set email alerts
|

Penetration Rate and Effectiveness Studies of Aggregated BESS for Frequency Regulation

Abstract: With the increased environmental concern, the photovoltaic (PV) generation capacity is growing in today's power systems. As the PV penetration rate increases, the intermittency and uncertainty of PV systems will cause frequency regulation issues. When rapid fluctuations take place, the system requires fast responding regulation to recover the frequency within a short period of time. Traditional power plants with slow dynamics are less capable of tracking the fast-changing regulation signal. In this context, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…Multi-hour/day simulations to study the BESSs impact on the grid are considered in [20,21,22,23,24]. In [20], the impact of a BESS on a small power system is evaluated with field tests by changing the parameters of PFC.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Multi-hour/day simulations to study the BESSs impact on the grid are considered in [20,21,22,23,24]. In [20], the impact of a BESS on a small power system is evaluated with field tests by changing the parameters of PFC.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In [22,23,24], the focus is on secondary frequency control, where BESSs are introduced in the simulations to improve the stability of the grid, and their performance is compared to Conventional Generation (CG).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, applying energy storage systems with photovoltaic systems is promising and a lot of attention and various studies are being performed in this field. Therefore, an encouraging research concept which opened new windows in the field of hybrid RE/ESS generation system is the concept of virtual inertia (VI) and virtual synchronous generator (VSG) [52][53][54][55][56][57][58]. In the VSG concept, a short term energy storage system should be added next to converters of renewable-based power generation systems.…”
Section: Operation and Regulation Of Dpsmentioning
confidence: 99%
“…Frequency response, especially in smaller grid systems, requires the very quick injection or withdrawal of real power [9]. While there are a number of ways to address this issue, fast response battery energy storage systems (BESSs) have been identified as one of the most promising technologies for this grid service [10], and several modeling studies have indicated the potential for BESSs to provide frequency regulation [11][12][13][14][15][16]. Other ancillary services have also been demonstrated to minimize daily operational cost as well as energy scheduling [17,18].…”
Section: Introductionmentioning
confidence: 99%